Small and informal enterprise development in deprived areas - Matsho, Jim (University of the Free State, 2024)
The research investigated small and informal enterprises' business problems and experiences in a deprived context of the King Cetshwayo District Municipality in northern KwaZulu-Natal within the forestry value chain. The research followed a qualitative approach using semi-structured interviews with entrepreneurs. An interview guide was used, and it is available both in English and iSiZulu. Most participants from the sample of 12 operate transport businesses that move timber from the forestry timber small-scale farmers' area(s) to the processing plants in the Richards Bay industrial complex. The data analysis provides the following themes: capacity building, finances, financial systems, machine(s), operational challenges, and records management. The study limitations include the following: study area size, small sample size, unavailability of participants, business conditions, and human capacity. The study found eight key challenges SMMEs face in deprived areas, with finance access being the main challenge, including mentorship, regulatory compliance, and economies of scale, among others identified. It was found that proper maintenance and implementation of financial systems are critical to the SMME ecosystem. The study provides twelve recommendations addressing the eight main findings to address the research question, which is as follows: dedicated funding for SMMEs in the forestry value chain, increased funding be made available for entrepreneurs, promotion of finance and accounting systems, additional trucking capacity for increased demand, improved efficiency and monitoring systems with the operation, upskill contractor personnel through HEIs, embark on capacity building programme focusing on locals, implementation of filling system and protocol(s), implementation of the Enterprise Development Program (EDP) for SMMEs inclusion, a dedicated mentorship program for the forestry value chain entrepreneurs, legislation introduction mainly targeted forestry SMMEs to reduce compliance costs and measurement of productivity. It also offers further research study area suggestions for future research projects. Lastly, the study concludes and reiterates that SMMEs drive sustainability, employment creation, and economic contribution in deprived areas.
Dissertation(MDS (Development Studies))--University of the Free State, 2024
Keywords: Deprivation; Forestry; Informal business; SMME; Sustainable development